Si-SiC oxidation barrier coating on 3D printed Si-SiC strut-based architectures deposited by electrophoretic deposition. Issue 5 (May 2023) - Bianchi, Giovanni; Di Mauro, Antonio; Ferrari, Luca; Gianella, Sandro; Ortona, Alberto
Abstract: This work reports on the production and oxidation behavior at 1500 °C of SiC coated Si-SiC tetrakaidekahedron periodic structures. C-SiC lattices were first produced by 3D printing of polymers templates followed by the replica technique and pyrolysis. They were then coated by electrophoretic deposition (EPD) with submicron SiC particles. SiC particles were dispersed in water and deposited successfully on C–SiC structures by optimising voltage, frequency and duty cycle to minimize water electrolysis in the aqueous system. Different coating thicknesses were deposited on the substrates by varying the deposition time. Samples were infiltered with molten silicon, oxidized at 1500 °C and characterized.